2021
DOI: 10.3390/su13147981
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Transformational Leadership on Organizational Performance: Testing the Mediating Effects of Knowledge Management

Abstract: Transformational leadership is a sustainable and exemplary form of leadership that liberates subordinates’ ideas, enables subordinates to view problems from a different perspective, helps adaptation to changing environments, and increases Human Resources Management effectiveness in public and service institutions. The effects of transformational leadership on organizational performance by means of knowledge management have been examined in this study on the northern Cyprus Security Forces. In addition, the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 126 publications
(158 reference statements)
1
8
0
Order By: Relevance
“…One of the purposes of the balanced scorecard is to measure how organizational performance is affected individually. Organizations that seek to increase their performance must adapt to the information age's environment in which individuals can develop knowledge [82].…”
Section: Discussionmentioning
confidence: 99%
“…One of the purposes of the balanced scorecard is to measure how organizational performance is affected individually. Organizations that seek to increase their performance must adapt to the information age's environment in which individuals can develop knowledge [82].…”
Section: Discussionmentioning
confidence: 99%
“…According to Nabi et al (2022), transformational leadership is the process by which managers and employees foster righteousness, encouragement, inspiration, and drive in their pursuit, acquisition, and sharing of knowledge. The transformational leader must create a knowledge-centric system and devise innovative transformational approaches by gathering both explicit and implicit data from within the firm (Kılıç and Uludağ, 2021). Innovative work behavior encompasses an individual's aptitude for generating novel and potentially valuable ideas, as well as the capacity to effectively implement those ideas into practice .…”
Section: Document Analysismentioning
confidence: 99%
“…Yeh, Lai and Ho (2006) led the research to discover the impact of knowledge management dynamics, prompting better organizational capacity in implementing, developing, and maintaining suitable practices that would enable firms to select, organize, find, transfer, and disseminate significant information for better performance (Demerouti & Bakker, 2011). Research has shown that knowledge management positively affected organizational performance (Al-Bahussin & Elgaraihy, 2013;Kinyua, 2015;Kılıç & Uludağ, 2021). Thus, knowledge management enhances the quality of decision-making and increases organizational performance sustainability (Mosconi & Roy, 2013).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Hence, the recent research proposes the following hypothesis: H 6 : Knowledge management has a significant and positive effect on organizational performance. Knowledge management was found to be the mediator that provided a beneficial outcome to the organization and the organization's individuals (Al-Bahussin & Elgaraihy, 2013;Iqbal & Malik, 2019;Kılıç & Uludağ, 2021). Some investigations exhibited that knowledge management had a mediator role linking HRM practices and organizational performance (Al-Tit, 2016; Gope et al, 2018).…”
Section: Hypotheses Developmentmentioning
confidence: 99%